One historical truth in the korkyt legend - Alkuat Kazakbaev, Ruslan Alimbekov, (Opción, 2019)
This article describes the historical reality of the legend of Korkyt Ata, one of the most famous people who contributed to the development of the worldview and culture of the Turkic peoples by using historical, philosophical, literary-folklore, and archaeological methods. As a result, exaggerating the power of art, describing everything by metaphorical expressions can be seen in the folk epic, epos, and historical minds of people. In conclusion, in the history of the Turkic peoples, which inhabited Great Steppe, totem concepts and beliefs were reflected both in the political history of the people and in the cultural and ideological regard.